The Circadian Clock Improves Fitness in the Fruit Fly, Drosophila melanogaster - Horn, Melanie; Mitesser, Oliver; Hovestadt, Thomas; Yoshii, Taishi; Rieger, Dirk; Helfrich-Förster, Charlotte (Frontiers in Physiology, 2019)
It is assumed that a properly timed circadian clock enhances fitness, but only few studies have truly demonstrated this in animals. We raised each of the three classical Drosophila period mutants for >50 generations in the laboratory in competition with wildtype flies. The populations were either kept under a conventional 24-h day or under cycles that matched the mutant’s natural cycle, i.e., a 19-h day in the case of pers mutants and a 29-h day for perl mutants. The arrhythmic per0 mutants were grown together with wildtype flies under constant light that renders wildtype flies similar arrhythmic as the mutants. In addition, the mutants had to compete with wildtype flies for two summers in two consecutive years under outdoor conditions. We found that wildtype flies quickly outcompeted the mutant flies under the 24-h laboratory day and under outdoor conditions, but perl mutants persisted and even outnumbered the wildtype flies under the 29-h day in the laboratory. In contrast, pers and per0 mutants did not win against wildtype flies under the 19-h day and constant light, respectively. Our results demonstrate that wildtype flies have a clear fitness advantage in terms of fertility and offspring survival over the period mutants and – as revealed for perl mutants – this advantage appears maximal when the endogenous period resonates with the period of the environment. However, the experiments indicate that perl and pers persist at low frequencies in the population even under the 24-h day. This may be a consequence of a certain mating preference of wildtype and heterozygous females for mutant males and time differences in activity patterns between wildtype and mutants.